The Hawaiian goose : an experiment in conservation - Kear, Janet (Poyser monographs, 2010)
Dr Janet Kear, Assistant Director of the Wildfowl Trust and Curator of its Martin Mere Reserve, and Professor Andrew Berger of the University of Hawaii, have written a timely and absorbing account of the recent history of the Hawaiian Goose, or Nene, its descent to near extinction, its eleventh hour rescue and current restoration to the wild. The species declined from an estimated population of 25,000 in Hawaii in the 18th century to less than fifty birds in the 1940s. Today, thanks largely to the extended breeding programmes at Slimbridge and Pohakuloa, there are probably more than 2000 Hawai.